Environmental forensics fundamentals : a practical guide - Petrisor, Ioana Gloria, 1969- (CRC Press, 2014)
"This book provides state of the art information in the emerging field of environmental forensics. Exemplified through real case studies, it provides an up-to-date overview of main environmental forensics techniques. Emphasizing methodologies targeting both the contaminant and the associated environmental matrix, it presents a variety of challenging situations and offers appropriate solutions through practical application of forensic techniques. The book is meant to function as a "road map" providing users with a comprehensive forensic toolkit and the knowledge of how to use it in challenging situations"-- Provided by publisher.
Keywords: Environmental forensics.; elektronické knihy; electronic books